Last samurai standing. 2 - Imamura, Shōgo, 1984- (Kodansha USA Publishing, LLC, 2025)
"The year 1878--the 11th year of the Meiji era in Japan, and more than a decade since the samurai were stripped of their privileges and swords outlawed on public streets. A mysterious flyer appears in all corners of the land, luring those skilled in martial arts to Kyoto with the promise of riches beyond common imagination. As warriors deprived of purpose flock to the appointed place at the appointed time, what awaits them is no ordinary task but an all-out war--against each other! Perfect for fans of Shogun, Golden Kamuy, and Blade of the Immortal!"--